Knowledge Relationship With Bronchial Asthma Prevention Effort At Home Regional General Hospital (RSUD) Kaur Year 2022 - Julia, Vera Mita; Handayani, Tuty; Retni, Retni (Journal of International Public Health, 2022)
Asthma is a serious global health problem and needs to be addressed. The incidence of asthma sufferers based on data from the Kaur Regional General Hospital (RSUD) for 2019-2021 found that the incidence of recurrence of bronchial asthma in 2019 was 40 people, in 2020 there were 50 people, and in 2021 there were 63 people. The purpose of this study was to find out the relationship between knowledge and efforts to prevent bronchial asthma at Kaur Hospital, Kaur Regency in 2022. The research design used is a type of quantitative research with a cross sectional approach. The data collection tool uses a questionnaire as a research instrument. The number of samples is 63 people in total sampling. Data analysis was performed univariately and bivariately (using the chi square test with α=0.05). The results showed that almost some of the respondents had good knowledge, most of the respondents were good at preventing bronchial asthma and there was a significant relationship between knowledge and efforts to prevent bronchial asthma at Kaur Hospital, Kaur District in 2022. It is hoped that Kaur Hospital can improve health promotion at the hospital regarding the prevention of bronchial asthma. Asthma is a serious global health problem and needs to be addressed. The incidence of asthma sufferers based on data from the Kaur Regional General Hospital (RSUD) for 2019-2021 found that the incidence of recurrence of bronchial asthma in 2019 was 40 people, in 2020 there were 50 people, and in 2021 there were 63 people. The purpose of this study was to find out the relationship between knowledge and efforts to prevent bronchial asthma at Kaur Hospital, Kaur Regency in 2022. The research design used is a type of quantitative research with a cross sectional approach. The data collection tool uses a questionnaire as a research instrument. The number of samples is 63 people in total sampling. Data analysis was performed univariately and bivariately (using the chi square test with α=0.05). The results showed that almost some of the respondents had good knowledge, most of the respondents were good at preventing bronchial asthma and there was a significant relationship between knowledge and efforts to prevent bronchial asthma at Kaur Hospital, Kaur District in 2022. It is hoped that Kaur Hospital can improve health promotion at the hospital regarding the prevention of bronchial asthma.